PELAKSANAAN MODEL PROBING-PROMPTING PADA PELAJARAN SOSIOLOGI SISWA XI IPS 1 SMA NEGERI 3 PONTIANAK - Rasina, Rasina; Okianna, Okianna; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is entitled "Analysis of the Implementation of Prompting Probing Learning Models in Sociology Subjects in Class XI IPS 1 SMA Negeri 3 Pontianak". The purpose of this study was to find out how the lesson plan, implementation of learning, and sociology learning outcomes of the probing prompting model in class XI IPS 1 SMA Negeri 3 Pontianak. The method in this study uses a qualitative research method with a descriptive research form. The informants in this study were sociology teachers who taught class XI IPS 1 at SMA Negeri 3 Pontianak and three students from class XI IPS 1 at SMA Negeri 3 Pontianak. The results of this study indicate that in the implementation of sociology learning using the probing prompting model as a learning model with material about Social Problems that has been made in the Learning Implementation Plan (RPP) based on the provisions set by the government. In the implementation of sociology learning using this probing prompting model which consists of preliminary activities, core activities, and closing activities. The learning outcomes obtained in this study were through three observations with the acquisition of learning outcomes consisting of three domains, namely the cognitive domain (knowledge) obtained through daily tests, group assignment scores, and individual task scores, affective domain (attitude) obtained through spoken words.)